2015
DOI: 10.1080/08927022.2015.1048513
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glycerol on the binding of methotrexate toMycobacterium tuberculosisdihydrofolate reductase: a molecular modelling study

Abstract: 2015): The influence of glycerol on the binding of methotrexate to Mycobacterium tuberculosis dihydrofolate reductase: a molecular modelling study, Molecular Simulation, The enzyme, dihydrofolate reductase (DHFR), from Mycobacterium tuberculosis (mt-DHFR) is believed to be a potential drug target for the treatment of tuberculosis. The co-crystal structure of mt-DHFR bound with glycerol (GOL), NAPDH and methotrexate (MTX) reveals a GOL binding site on the enzyme. This GOL binding site could be very important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As a positive control, five known and Food and Drug Administration (FDA)-approved inhibitors that have inhibitory activity against the target protein and the natural substrate (dihydrofolate) were selected, all five inhibitors of reference have shown a good affinity toward the enzyme, the most potent one is MTX that showed the lowest value of affinity energy (–8.9 kcal/mol), this molecule is used usually as an anticancer drug, 7 based on the aforementioned information, MTX was taken as the inhibitor of reference in terms of energy score to compare its activity and potency with the 11 selected molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a positive control, five known and Food and Drug Administration (FDA)-approved inhibitors that have inhibitory activity against the target protein and the natural substrate (dihydrofolate) were selected, all five inhibitors of reference have shown a good affinity toward the enzyme, the most potent one is MTX that showed the lowest value of affinity energy (–8.9 kcal/mol), this molecule is used usually as an anticancer drug, 7 based on the aforementioned information, MTX was taken as the inhibitor of reference in terms of energy score to compare its activity and potency with the 11 selected molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of DHFR is the basis for the use of MTX as a cancer chemotherapy drug. 7 In our study, we approved the toxic profile of this drug using in silico approach, MTX was found to be in class 1 in toxicity level with an LD50 of 3 mg/ kg, which was approved by another study; a meta-analysis reported across Asian, Caucasian, pediatric, and adult patients that treats three systematic reviews on MTX-induced toxicity, 33 another research on MTX doses described that MTX is administered at doses ranged from 12 mg intrathecally and 20 mg/m 2 orally, or intravenously as weekly maintenance chemotherapy for all to doses as high as 33 000 mg/m 2 , higher given intravenously are defined as high-dose MTX (HDMTX) therapy that can cause significant toxicity, which not only leads to morbidity and occasional mortality but may also interrupt cancer treatment. 34 Searching for a non-toxic alternative drug that has a better affinity than MTX for h-DHFR was the second part of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation